The Economic Performance of the Nordic Countries - Czarny, Bogusław (Warsaw Forum of Economic Sociology, 2023)
In this article, utilizing the appropriate statistical data, I analyse the economic results of the Nordic countries i.e., Denmark, Finland, Iceland, Norway and Sweden. I begin from the Human Development Index (HDI). This index describes the objective conditions, impacting upon the incomes, health and levels of education, upon which the possibility of utilizing the natural capacities of persons depend. Then I make use of the subjective evaluations of the satisfaction from life. For this I look at the results of research undertaken in the context of the economics of happiness. In approaching another type of economic analysis I look at the behaviour of variables upon which economic efficiency and justice in the Nordic countries are directly dependent. I recognize the size of GDP per capita and innovation in the economy as efficiency indicators, and as indicators of justice I rely on the intergenerational mobility of earnings, the variability of incomes, the extent of poverty and also the situation in the labour market. I present the results of national economic management in the Nordic countries against the backdrop of economically developed countries (namely the countries of continental Europe, southern Europe, Great Britain and – the United States). The analysis shows that the societies of Denmark, Finland, Iceland, Norway and Sweden managed to achieve some of the best (if not the best) results in the management of their national economies. At the same time, it is noticed that differences in the economic performance in individual Nordic countries are relatively small.